2016
DOI: 10.1007/s10071-016-1011-4
|View full text |Cite
|
Sign up to set email alerts
|

Picture object recognition in an American black bear (Ursus americanus)

Abstract: Many animals have been tested for conceptual discriminations using two-dimensional images as stimuli, and many of these species appear to transfer knowledge from 2D images to analogous real life objects. We tested an American black bear for picture-object recognition using a two alternative forced choice task. She was presented with four unique sets of objects and corresponding pictures. The bear showed generalization from both objects to pictures and pictures to objects; however, her transfer was superior whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…The different rate of learning of the one black bear tested and the three gorillas tested here may point to the possibility of species differences in associating images of food and inedible objects to the outcome of receiving real food items. Interestingly, the same bear performed very well on tests of picture-object recognition (Johnson-Ulrich et al, 2016), whereas other gorillas have demonstrated conflicting patterns of results in such studies (Parron, et al, 2008). Whereas the gorillas could direct pointing to actual food items that represented larger quantities, they could not learn to touch images depicting the same quantity differences of the same food items.…”
Section: Discussionmentioning
confidence: 99%
“…The different rate of learning of the one black bear tested and the three gorillas tested here may point to the possibility of species differences in associating images of food and inedible objects to the outcome of receiving real food items. Interestingly, the same bear performed very well on tests of picture-object recognition (Johnson-Ulrich et al, 2016), whereas other gorillas have demonstrated conflicting patterns of results in such studies (Parron, et al, 2008). Whereas the gorillas could direct pointing to actual food items that represented larger quantities, they could not learn to touch images depicting the same quantity differences of the same food items.…”
Section: Discussionmentioning
confidence: 99%
“…However, Clark (2013) reviewed the field of marine mammal (primarily bottlenose dolphin and California sea lion, Zalophus californianus) cognition and proposed that knowledge of various species' cognitive skills could and should be used to develop appropriate cognitive enrichment. Cognitive research on other species could be applied in a similar fashion; for example we have a growing knowledge of the cognitive skills of elephants, Elephas maximus, Loxodonta africana (Foerder, Galloway, Barthel, Moore, & Reiss, 2011;Perdue, Talbot, Stone, & Beran, 2012;Plotnik, Lair, Suphachoksahakun, & de Waal, 2001), giant pandas, Ailuropoda melanoleuca (Dungl, Schratter, & Huber, 2008;Perdue, Snyder, Pratte, Marr, & Maple, 2009) and black bears, Ursus americanus (Johnson-Ulrich et al, 2016;Vonk & Beran, 2012;Vonk, Jett, & Mosteller, 2012). There has also been substantial work on the cognition (mainly physical cognition) of corvid birds (Clayton & Emery, 2005;Taylor, 2014).…”
Section: Cognitive Research As Enrichmentmentioning
confidence: 99%
“…Enhanced selective attention should in turn enhance survivorship over that of youngsters who learn only from direct experience with environmental stimuli. Whereas the cultural intelligence hypothesis might thus explain the relatively large brains and striking general intelligence observed in bears [36,[51][52][53] and certain other solitary carnivores (e.g. raccoons [54][55][56][57]), several troubling exceptions remain that this hypothesis cannot explain.…”
Section: Introductionmentioning
confidence: 99%